2014
DOI: 10.1038/srep04529
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Light Scattering Tracking of Gold Nanoparticles- bioconjugated Respiratory Syncytial Virus Infecting HEp-2 Cells

Abstract: Real-time tracking of virus invasion is crucial for understanding viral infection mechanism, which, however, needs simple and efficient labeling chemistry with improved signal-to-noise ratio. For that purpose, herein we investigated the invasion dynamics of respiratory syncytial virus (RSV) through dark-field microscopic imaging (iDFM) technique by using Au nanoparticles (AuNPs) as light scattering labels. RSV, a ubiquitous, non-segmented, pleiomorphic and negative-sense RNA virus, is an important human pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…10g demonstrates the utility of this technique in monitoring respiratory syncytial virus (RSV) infection in larynx epidermal cells using virus surface-labeled Au NPs. 225 The authors tracked RSV cell-entry kinetics and demonstrated that 13-nm Au NPs probes can serve as non-interfering, non-photobleaching dark-field imaging probes.…”
Section: Probing Cellular Interactions Of Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…10g demonstrates the utility of this technique in monitoring respiratory syncytial virus (RSV) infection in larynx epidermal cells using virus surface-labeled Au NPs. 225 The authors tracked RSV cell-entry kinetics and demonstrated that 13-nm Au NPs probes can serve as non-interfering, non-photobleaching dark-field imaging probes.…”
Section: Probing Cellular Interactions Of Nanoparticlesmentioning
confidence: 99%
“…i) Laser-ablation inductively coupled plasma mass spectrometry (ICP-MS) imaging (heatmap) of mouse fibroblasts (grayscale) incubated with Au (left) and Ag (right) nanoparticles. Reproduced with permission from (a) 207 , (b) 209 , (c) 243 , (d) 214 , (e) 217 , (f) 221 , (g) 225 , (h) 228 , and (i) 234 . Copyright (a) 2016 American Chemical Society, (b) 2014 Købler et al ., (c) 2015 Grant et al ., (d) 2014 Nature Publishing Group, (e) 2013 Nature Publishing Group, (f) 2014 Nature Publishing Group, (g) 2014 Nature Publishing Group, (h) 2016 Strohm et al ., and (i) 2012 American Chemical Society.…”
Section: Figmentioning
confidence: 99%
“…Owing to their unique physicochemical properties, varied and tailorable shapes, sizes and chemical compositions, gold nanostructures make excellent candidates for molecular imaging and, potentially, therapy of various diseases, including cancer [155, 156], cardiovascular disease [157159], viral infections [160162], and others. [163, 164] Gold nanoparticles (AuNPs) display excellent biocompatibility as gold is relatively inert in biological environments.…”
Section: Radiolabeled Nanomaterials For Cancer Theranosticsmentioning
confidence: 99%
“…However, for typical applications where sub-picomolar detection is sufficient, the simplicity of direct oligonucleotide quantification assays makes them more attractive for various applications. [29][30][31][32][33][34][35][36][37] including SNP detection [38][39][40][41], as well as for gene delivery [42] and molecular imaging [43,44]. In applications typical for oligonucleotide sensing the analyte induces the agglomeration of AuNPs by hybridization, resulting in a red shift of the nanoparticle plasmon peak [45].…”
Section: Introductionmentioning
confidence: 98%